PENYELESAIAN SENGKETA HUTANG PIUTANG DI KALANGAN MASYARAKAT TALOHEN HULU KELURAHAN AMPAH KOTA KABUPATEN BARITO TIMUR - Syarifuddin, Syarifuddin; Dakhoir, Ahmad; Azizah, Sri Dewi Nur (AL-QARDH, 2016)
Debt is one of the activities muamalah are allowed in Islam. Most people choose the wrong place when the event of default of borrowing and cause disputes often occur crime and immoral actions against the borrower. Unlike the case with accounts payable disputes that occur in society Talohen Hulu. The purpose of this study was to determine the background of the debts, the form of contract debts and settlement of disputes when the event of default (wanprestasi)in among community of Talohen Hulu village of Ampah City district of East Barito.